2002
DOI: 10.1083/jcb.200111047
|View full text |Cite
|
Sign up to set email alerts
|

Myelin-associated glycoprotein and myelin galactolipids stabilize developing axo-glial interactions

Abstract: We have analyzed mice that lack both the myelin-associated glycoprotein (MAG) and the myelin galactolipids, two glial components implicated in mediating axo-glial interactions during the myelination process. The single-mutant mice produce abnormal myelin containing similar ultrastructural abnormalities, suggesting that these molecules may play an overlapping role in myelin formation. Furthermore, the absence of the galactolipids results in a disruption in paranodal axo-glial interactions, and we show here that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
90
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 49 publications
(93 reference statements)
7
90
0
2
Order By: Relevance
“…Interestingly, whereas gangliosides are produced most prominently in neurons, production of the gala-series is largely restricted to myelin-producing cells. This finding suggests that the ganglio-and gala-series of glycosphingolipids may play parallel roles in promoting axonal-glial interactions, which is consistent with observations that concomitant deletion of galaseries glycosphingolipids and MAG genes in mice produces a more severe phenotype (34).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, whereas gangliosides are produced most prominently in neurons, production of the gala-series is largely restricted to myelin-producing cells. This finding suggests that the ganglio-and gala-series of glycosphingolipids may play parallel roles in promoting axonal-glial interactions, which is consistent with observations that concomitant deletion of galaseries glycosphingolipids and MAG genes in mice produces a more severe phenotype (34).…”
Section: Discussionsupporting
confidence: 89%
“…The prominent paranodal components contactin, NF-155, Caspr, and sulfatide [interacts with versican in vitro (Miura et al, 1999)] seem also not necessary for the selective deposition and binding of versican V2 at the nodes. In CGT-null mice, they are all virtually absent from the severely disturbed terminal glial loops of the paranodes (Poliak et al, 2001;Marcus et al, 2002). Nevertheless, versican V2 and TnR accumulate normally in CGT mutants, as demonstrated by our immunohistochemical analyses.…”
Section: Discussionsupporting
confidence: 68%
“…Similar phenotypes were observed at the paranodes in CGT mutants (18,19). CGT encodes an enzyme that is needed for the biosynthesis of two important myelin lipids, galactocerebroside and sulfatide (10,(18)(19)(20)(21).…”
supporting
confidence: 59%
“…It has been shown that NCP1 and CGT mice also have disrupted AGJs in the peripheral nerves (5,19). We have not observed axonal swellings in the sciatic nerves of NCP1 and CGT mutants at the age that we analyzed the animals (P25).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation